The Influence of Organizational Culture and Competence on Employee Performance at Public Appraisal Service Office Andi Tiffani and Partners Through Motivation as a Mediation Variable - Noniulpa Noniulpa; Aslam Mei Nur Widigdo (Dinasti Publisher, 2023)
This study aims to determine the effect of competence and organizational culture on the performance of employees of the Public Appraiser Service Office Andi Tiffani and Partners (KJPP ATR). This study used a quantitative method with a total sample of 53 employees. Samples were taken from the entire population or using saturated sampling techniques, namely all KJPP ATR employees. The data analysis method uses the Structural Equation Model (SEM) with the SmartPLS analysis tool. The results showed that competence had a significant positive effect on employee performance, organizational culture had a significant positive effect on employee performance, competence had a significant positive effect on work motivation, organizational culture had a significant positive effect on work motivation.